2015
DOI: 10.1097/bot.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Fix It or Discard It? A Retrospective Analysis of Functional Outcomes After Surgically Treated Patella Fractures Comparing ORIF With Partial Patellectomy

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 17 publications
0
25
0
2
Order By: Relevance
“…The patient-reported functional outcome scores in this series were higher than those reported in the literature for tension band fixation and patellectomy. 5,9,24 The mean KOS-ADLS in our series was 83.9. Bonnaig et al reported mean KOS-ADLS scores of 64.1 and 62.1 for ORIF and patellectomy, respectively.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The patient-reported functional outcome scores in this series were higher than those reported in the literature for tension band fixation and patellectomy. 5,9,24 The mean KOS-ADLS in our series was 83.9. Bonnaig et al reported mean KOS-ADLS scores of 64.1 and 62.1 for ORIF and patellectomy, respectively.…”
Section: Discussionmentioning
confidence: 51%
“…Tension band constructs employ a variety of implants including Kirschner wires, malleable steel wires, cannulated screws, cables, or suture, with no implant or combination of implants proving to be superior to another. 5,9,[18][19][20][21][22][23] Partial patellectomy with advancement of the patellar tendon remains the most common treatment when there is significant comminution of the inferior pole. Currently, there is no well-established method to effectively treat comminuted fractures and those that involve the inferior pole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I nferior pole fractures of the patella account for 9.3%-22.4% of all patellar fractures 2 , and various surgical procedures to preserve fragments of the inferior pole is gaining popularity recently [8][9][10]14 . However, it remains doubtful which surgical technique is superior.…”
Section: Discussionmentioning
confidence: 99%
“…Her ne kadar amaç patellanın korunması olsa da, kısmi patellektomi ile tespitin benzer sonuçları olduğu da bildirilmiştir (Şekil 1). [14] Patellektomi sonrasında hareket kısıtlılığı, diz instabilitesi, ekstansör mekanizmada belirgin güç kaybı, yürüme ve merdiven çıkmada zorluk yaşanması nedeniyle, patellektomi en son tercih edilen kurtarıcı bir cerrahi yöntemdir. Patella kırıklarında geç kaynama ve kaynamamada kemik grefti kullanımı konusunda, bildirilen birkaç olgu dışında ayrıntılı bilgi bulunmamaktadır.…”
Section: Cerrahi Tedaviunclassified